Build a Rectangular Patch Single Microstrip Antenna with Aperture Coupled for Wifi Application 2.4 Ghz - Rizka Kurnia Indrianti (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2019)
Wifi technology is a means of obtaining information in a fast way, to strengthen the signal, for that it is required that the functioning antenna emit and receive electromagnetic waves in which contained the information signal. A wide range of antennas have been developed for a wide range of applications, one of which is a microstrip antenna. Microstrip antennas have small characteristics, are lightweight, thin, easy to fabricate, and can be used at very long distances. The results of single rectangular patch microstrip antenna measurements indicate that the antenna can work optimally with a frequency of 2,440 GHz, has a return loss-22,182 dB value, VSWR 1,169 value, 0.3452 dB bandwidth value, LOS-45.6 dBm power value with Percentage upload is 97% higher than the reference antenna and the download percentage is 88% higher than the reference antenna, NLOS-79 dBm value with a percentage upload of 33% compared to the reference antenna and the download percentage 12% higher than the Reference antenna, for the range of distances capable of receiving signals up to 120 meters with a percentage of percentage of is 16% higher than the reference antenna.